Enhancing the ecosystem approach for the fishery for Antarctic krill within the complex, variable, and changing ecosystem at South Georgia. (10th June 2021) - Trathan, P N; Fielding, S; Hollyman, P R; Murphy, E J; Warwick-Evans, V; Collins, M A
Abstract: The objective of the ecosystem approach to fisheries management is to sustain healthy marine ecosystems and the fisheries they support. One of the earliest implementations was in the Southern Ocean, where decision rules and stock reference points were developed for managing the Antarctic krill fishery, together with an ecosystem-monitoring programme intended to aid management decisions. This latter component has not been incorporated directly into management, so here, we consider variability in the krill fishery at South Georgia, relating it to physical and biological monitoring indices, finding sea surface temperature to be a key correlate with both annual catch and long-term biological indices. Some indices from krill predators showed significant positive relationships with krill harvesting in the preceding winter, presumably indicative of the importance of winter foraging conditions. We explore how ecological structure affects results, examining two monitoring sites 100 km apart. Results suggest different biological conditions at the two sites, probably reflecting different scales of ecosystem operation, emphasizing that an appreciation of scale will enhance krill fishery management. Finally, in reviewing different drivers of ecological change, we identify important additional monitoring that would help better reflect ecosystem status, improve the utility of CEMP, providing information necessary for the ecosystem approach at South Georgia.